Modification of the Four-Step Motorcycle Camshaft Used in Making Salwa Cars (Go Card) - Dwi Dwi Jatmoko; Rudi Kurniawan; Aci Primartadi; Suyitno; Arif Susanto (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2021)
To meet the needs of racing, both drag bike racing and road races, vehicles or motorcycles with conditions still standing are not enough. Therefore, it is necessary to modify certain parts, including modifying the chassis, body, and engine. The three parts are very related. Of the three parts, the most priority is modifying the engine because the engine is the main factor in a vehicle or motorcycle. What is needed in modifying the engine is improving engine performance or maximizing engine performance. In this study, the author chose a four-stroke kharisma motorcycle because the modification did not require many changes from the standard conditions. Drag bike racing and road racing have similarities in modifying the engine. Only the difference is in terms of calculating engine endurance. Drag bike racing does not need long engine endurance because it only drives on straight tracks, while road races must think about engine endurance because the engine works in rough terrain conditions varies.